2007
DOI: 10.1093/carcin/bgm073
|View full text |Cite
|
Sign up to set email alerts
|

Tagging SNPs in non-homologous end-joining pathway genes and risk of glioma

Abstract: Ionizing radiation is known to cause DNA damage, including single-strand and double-strand DNA breaks (DSBs), and the unrepair of DNA damage, particularly DSBs, may cause chromosome aberrations. Although the etiology of gliomas remains unclear, exposure to ionizing radiation has been identified as the only established risk factor. We hypothesized that polymorphisms of candidate genes involved in the DSBs repair pathway may contribute to susceptibility to glioma. We used a haplotype-based approach to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 36 publications
4
63
0
Order By: Relevance
“…We have listed about 20 epidemiological studies reporting positive associations between DNA repair polymorphisms and cancer risk (Table 1 [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] ). Only a small proportion of studies were large (five studies were more than 500 pair cases and controls) and population based; however, some consistencies in results are apparent.…”
Section: Pbts Molecular Epidemiologic Studies With Focus On Dna Repairmentioning
confidence: 99%
“…We have listed about 20 epidemiological studies reporting positive associations between DNA repair polymorphisms and cancer risk (Table 1 [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] ). Only a small proportion of studies were large (five studies were more than 500 pair cases and controls) and population based; however, some consistencies in results are apparent.…”
Section: Pbts Molecular Epidemiologic Studies With Focus On Dna Repairmentioning
confidence: 99%
“…In our previously published studies, we have demonstrated that some representative tSNPs of genes involved in the NHEJ pathway may modulate risk of gliomas. 23,24 Also, these results suggest that the genetic interaction between DNA repair genes may play an important role in the etiology of gliomas.…”
Section: Discussionmentioning
confidence: 77%
“…23,24 Briefly, all subjects, including case and control groups, were unrelated Han Chinese people from Shanghai City and its surrounding regions in east China. Patients newly diagnosed with pathologically confirmed gliomas were recruited into study group between October 2004 and May 2006 at the Department of Neurosurgery of Huashan Hospital of Fudan University, Shanghai, China.…”
Section: Study Populationmentioning
confidence: 99%
“…However, the results indicated possible associations between combinations of XRCC1 and XRCC3 SNPs and the risk of glioma development, as carriers of both homozygous variant genotypes, i.e., XRCC1 Gln399Gln and XRCC3 Met241Met were associated with a three-fold increased risk of glioma (OR = 3.18;95% CI,). In a haplotype-based approach in a Chinese population, Liu et al (2007) investigated the role of 22 tagging SNPs (tSNPs) of XRCC5, XRCC6 and XRCC7. They found that glioma risk was significantly associated with three of the XRCC5 tSNPs (rs828704, rs3770502 and rs9288516, P = 0.005, 0.042 and 0.003, respectively), one XRCC6 tSNP (rs6519265, P = 0.044), and none of the XPCC7 tSNPs in a single-locus analysis.…”
Section: Molecular Marker Clinical Significancementioning
confidence: 99%